Studi Analisis Altman Z-Score Sebagai Indikator Prediksi Kebangkrutan di PT XYZ (Jurnal Riset Manajemen dan Akuntansi, 2025)
This study aims to evaluate the bankruptcy potential of PT XYZ by applying the Altman Z-Score method as a predictive tool for assessing the company’s financial health. The Z-Score model integrates several key financial ratios, including working capital to total assets, retained earnings to total assets, earnings before interest and taxes (EBIT) to total assets, and the book value of equity to total liabilities, to generate a score that reflects the level of bankruptcy risk. The analysis is based on secondary financial data from PT XYZ’s annual reports over the past five years (2019–2023) and is conducted using a quantitative approach. The results indicate that PT XYZ mostly falls within the grey area category, except in 2021, when the score dropped into the distress zone, signaling high bankruptcy risk. This condition reflects the company's unstable financial position and a potential for facing financial distress. Dependence on government financial assistance and volatility in equity structure are identified as the main factors influencing the fluctuation in the Z-Score values.